A design framework for the mass customisation of custom-fit bicycle helmet models - Thierry, Ellena; Mustafa, Helmy; Subic, Aleksandar; Pang, Toh Yen (Elsevier B.V., 2018)
Mass customisation (MC) can provide significant benefits to the customers. For example, custom-fit design approaches can improve the users’ perceived comfort of products where the fit is an important feature. MC can also bring major value to the producers, where for instance, premium prices can be implemented to the products. Research show that MC can bring competitive advantages especially when the system is new. It is therefore surprising that MC of helmets has not been studied more extensively, especially given the advances in 3D scanning, computational analyses, parametric design, and additive manufacturing techniques. The purpose of this study was to present a novel MC framework for the design of custom-fit bicycle helmet models. In the proposed design framework, we first categorized a subset of the Australian population into four groups of individuals based on their similar head shapes. New customers were then classified inside one of these groups. The customisation took place inside these groups to ensure that only small variations of the helmet liner were implemented. During the design process, the inside surfaces of a generic helmet model was modified to match the customer's head shape. We demonstrated that all the customized models created complied with the relevant drop impact test standard if their liner thickness was between the worst and best case helmets of each group. Fit accuracy was verified using an objective evaluation method. Future work should include detailed description of the manufacturing methods engaged in our MC framework.